Developing a quality framework of project management eLearning materials as part of blended learning methodology in a higher education learning institution - Deshinta, Arrova Dewi; Hafizah Nor, Abu Hassan; Zaidatol Haslinda, Abdullah Sani; Premylla, Jeremiah; Che Fuzlina, Fuad; Kannan, Ponkoodalingam (Academic Publishing International Limited, 2012)
Project Management is one of the essential subjects in the Faculty of Engineering and Information Technology INTI International University Malaysia that offered to all programs available from Diploma, Undergraduate and Postgraduate study. The primary goal of Project Management subject is to expose students to professional project management practices. The objectives typically include not only teaching theory, terms, definitions and new concepts related to the subject but also the transfer of new technical skills in using and applying specialized software as well as managerial skills dealing with people (interpersonal communications theory, dialogue, critical thinking and analysis skills, leadership theory, organizational theory, and team building). The CHAOS Report in 1995 providing the results of a survey which gathered data on reasons for Information Technology project failures.